Telomerase-based vaccines: a promising frontier in cancer immunotherapy - Sogand Vahidi; Arefeh Zabeti Touchaei (Cancer Cell International)
Abstract Telomerase, an enzyme crucial for maintaining telomere length, plays a critical role in cellular immortality and is overexpressed in most cancers. This ubiquitous presence makes telomerase, and specifically its catalytic subunit, human telomerase reverse transcriptase (hTERT), an attractive target for cancer immunotherapy. This review explores the development and application of telomerase-based vaccines, focusing on DNA and peptide-based approaches. While DNA vaccines demonstrate promising immunogenicity, peptide vaccines, such as UV1, UCPVax, and Vx-001, have shown clinical efficacy in certain cancer types. Recent advancements in vaccine design, including multiple peptides and adjuvants, have enhanced immune responses. However, challenges remain in achieving consistent and durable anti-tumor immunity. Accordingly, we discuss the mechanisms of action, preclinical and clinical data, and the potential of these vaccines to elicit robust and durable anti-tumor immune responses. This review highlights the potential of telomerase-based vaccines as a promising strategy for cancer treatment and identifies areas for future research.